Teacher Performance Evaluation: A Holistic Approach to Improving the Quality of Education in Elementary Schools - Susanto, Ratnawati; Agustina, Noni; Mujazi, Mujazi; Yulhendri, Yulhendri; Nasution, Evi Syafrida (Mimbar Sekolah Dasar, 2025)
The lack of teacher performance assessment at the elementary school level which only focuses on quantitative aspects such as attendance and administrative completeness, so that it has not been able to describe the pedagogical, personal, and professional competencies of teachers as a whole. The urgency of this research, considering the strategic role of teachers in improving student learning outcomes and contributing to the advancement of national education. The purpose of the study is to analyse a comprehensive and sustainable teacher performance assessment system, which integrates pedagogical, personality, and student learning outcomes. The method used is a mixed-methods approach, including surveys, observations, and interviews, with a sample of 300 people from elementary schools in Jakarta and its surroundings that have implemented a comprehensive assessment system. Data collection techniques include questionnaires, observations, and documentation, while data analysis is carried out using descriptive statistics, t-tests, and content analysis. The results of the study indicate that a holistic assessment system can significantly increase student motivation, competence, and learning outcomes. The conclusion of the study states that comprehensive evaluation can improve teacher professionalism and the quality of education in general, with important implications for the development of continuing professional education and training policies.